'Therefore They Shouldn't Exist': The Carter Administration, the 'Israel Lobby' and the Sinai Settlements. Issue 1 (2nd January 2020) - Ben-Ephraim, Shaiel
Abstract: The Israeli settlements in Sinai could have been a fatal obstacle to Egyptian–Israeli peace, but the Jimmy Carter administration overcame it. The established narrative of how Israel ceded the Sinai settlements focuses on the Camp David summit. However, the real battle over the fate of the settlements was fought previously. In February–April 1978, the Carter administration attempted to turn pro-Israeli supporters in the United States against the Israeli position, according to which the Sinai settlements should remain in place. The Menachem Begin government mobilized to counter that push but lost the battle. Contrary to his image as an awkward political operator, Carter won over supporters of Israel effectively. The case raises questions regarding the oft-mentioned role of the 'Israel lobby' in preventing peace.